The Use of Google Translate on Writing Assignments of English for IT Professional Class - Ratna Widya Iswara; Yoyok Sabar Waluyo; Dinda Kadarwati (Journal on Education, 2024)
This study aims to investigate the way in which Google Translate is used in practice by university students in the Information and Technology (IT) context. The research method used in this study is a descriptive design with a qualitative approach. 24 first-year students of non-English department taking English for IT Professional class are involved in this study. The tools used in this study were questionnaires and interviews. The results showed that students found Google Translate useful to support their academic studies, especially in doing writing assignments. However, they always needed to refine the grammar and logical structure of the translation. They sometimes also encounter difficulties in translating technical terms of the IT context. Google Translate has several roles in supporting students' writing skills with several positive and negative effects that affect their writing activities. In conclusion, the findings suggest that students use the technology of Google Translate in strategic ways to enhance their abilities in the English language.